Emotional Intelligence and Learning Interest in Islamic Religious Education and Character Building among Students at High School - Nuriski Hairuniska; Siti Zulaikhah; Zahra Rahmatika (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Learning interest is a critical determinant of students' success in the instructional process. In practice, however, many students continue to display low enthusiasm, limited concentration, and minimal engagement during Islamic Religious Education and Character Building (PAI and BP) lessons. Emotional intelligence has been proposed as a factor associated with this problem. This study examined the relationship between emotional intelligence and learning interest among students enrolled in PAI and BP at High School 3 Bandar Lampung, Indonesia. A quantitative correlational, ex post facto design was employed. The population consisted of 233 tenth-grade students, from which 70 respondents were drawn using Slovin's formula (10% margin of error) and a simple random sampling technique. Data were collected through a validated and reliable Likert-type questionnaire and analyzed using Kolmogorov-Smirnov normality tests, linearity tests, and Pearson product-moment correlation. The analysis yielded a correlation coefficient of r = 0.460 with a significance value of p = 0.000 (p < 0.05), indicating a statistically significant, positive relationship of moderate strength between emotional intelligence and learning interest. Students with higher emotional intelligence tended to report higher learning interest, and vice versa. These findings suggest that emotional intelligence plays a meaningful role in fostering learning interest and should be considered in efforts to improve the quality of Islamic religious education instruction.